Customer profitability, a case study - Arndís Arnardóttir 1985- (2018)
The tourism industry is an important field and one out of ten jobs in the world are related to the tourism industry. The tourism industry in Iceland is currently blooming, forecasts demonstrate that over the next years the industry will keep on blooming. The tourism industry is important for companies in Iceland and with this increase in travelers to Iceland service companies are increasing and expanding. Therefore, it is especially important that companies within the industry understand all associated costs related to the customers they serve and can measure the profitability of their customers. The topic of this thesis is a case study regarding the customer profitability (CP) of a service company in Iceland that provides services to tourists. The calculations of CP are provided with the accounting system Time-driven activity-based costing (TDABC). The findings in the case study revealed that an accounting system like the TDABC system can help companies identify profitability of customer groups and single customers. The TDABC system helps identify all costs associated with a company´s operations and allocates both direct and indirect costs in time units to each activity provided by company. The calculations provided with the TDABC system can help managers improve decision making regarding pricing and budgeting. Companies can increase their profit by having relevant informations on the actual costs associated with the services provided. The TDABC system is easy to implement and update. Therefore, service companies could benefit from the knowledge the model provides, improve their operations and understand the profitability of the customers that they serve. Beiðni um lokun verkefnis til maí 2023